REDUPLIKASI DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Maryansih, Reka; ', Charlina; ', Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses reduplication, reduplication types, and the meaning contained in the novel reduplications Tenggelamnya Kapal Van Der Wijck karya Hamka. This study aimed to describe the types of reduplication and meaning in the novel reduplications Tenggelamnya Kapal Van Der Wijck karya Hamka. This study is a qualitative research and descriptive method. Techniques used in data collection in this study is engineering documentation and technical notes. Data that has been found by reading and then analyzed by several stages of identifying the type, classifying the data, analyze the data and make inferences. Data sourced from reduplication found that novel serve as a reference in the study. The object of this research that says that experiencing reduplication. In this study there were 321 data regarding the type of reduplication, reduplication of data across 111, 122 partial reduplication of data, the data reduplication affixed 82, and 6 to change the data reduplication phonemes. On the meaning of reduplication there are as many as 148 of data, 10 data contained in reduplications meaningful assortment, 50 meaningful data plural, 17 meaningful data many times or repeatedly, 31 meaningful data are taking place or carried out continuously, 15 meaningful data, 5 meaningful data relaxing, very meaningful data 3, 16 or superlative most meaningful data, and the first meaningful data specificity.Key Words: Reduplication, novel Tenggelamnya Kapal Van Der Wijck.